2016
DOI: 10.1002/jpln.201500533
|View full text |Cite
|
Sign up to set email alerts
|

Nodulation and root growth increase in lower soil layers of water‐limited faba bean intercropped with wheat

Abstract: Below‐ground niche complementarity in legume–cereal intercrops may improve resource use efficiency and root adaptability to environmental constraints. However, the effect of water limitation on legume rooting and nodulation patterns in intercropping is poorly understood. To advance our knowledge of mechanisms involved in water‐limitation response, faba bean (Vicia faba L.) and wheat (Triticum aestivum L.) were grown as mono‐ and intercrops in soil‐filled plexiglass rhizoboxes under water sufficiency (80% of wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 40 publications
3
12
0
Order By: Relevance
“…Similar finding have been reported by Usharani et al, 14 and by Gar Alalma et al 15 These authors have reported first order reaction kinetics for the degradation and mineralization of chlorinated pesticides and insecticides and other various water pollutants by photocatalytic ozonation. [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] The results, shown in figure 5, demonstrates that the optimal conditions for imazapyr degradation with photocatalytic ozonation is neutral pH. On the other hand, the combination of two oxidation systems, ozonation and photocatalysis, for water treatment under optimal conditions are reported to have increased oxidation efficiencies (synergy) compared to the sum oxidation efficiencies of these two oxidation systems separately.…”
Section: Effect Of Ph Influence On Imazapyr Degradationmentioning
confidence: 98%
See 4 more Smart Citations
“…Similar finding have been reported by Usharani et al, 14 and by Gar Alalma et al 15 These authors have reported first order reaction kinetics for the degradation and mineralization of chlorinated pesticides and insecticides and other various water pollutants by photocatalytic ozonation. [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] The results, shown in figure 5, demonstrates that the optimal conditions for imazapyr degradation with photocatalytic ozonation is neutral pH. On the other hand, the combination of two oxidation systems, ozonation and photocatalysis, for water treatment under optimal conditions are reported to have increased oxidation efficiencies (synergy) compared to the sum oxidation efficiencies of these two oxidation systems separately.…”
Section: Effect Of Ph Influence On Imazapyr Degradationmentioning
confidence: 98%
“…The optimal amount of Hombikat UV 100 agrees well with reported results by other authors. [14][15][16][17][18][19][20][21][22][23][24][25][26] This improvement can be attributed to the increasing of active sites by providing more TiO 2 particles, which plays the semiconductor role in the photocatalysis process. Consequently, the formation of electron-hole pairs and reactive hydroxyl radicals on the surface of semiconductor increased, which improved the oxidation of imazapyr into other intermediates.…”
Section: Effect Of Tio 2 Dose On Imazapyr Degradationmentioning
confidence: 99%
See 3 more Smart Citations